2022
DOI: 10.3390/children9091396
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Post-Operative Outcomes in Children with Very Severe Obstructive Sleep Apnea

Abstract: Available information on clinical characteristics and post-operative outcomes in children with very severe obstructive sleep apnea (OSA) is limited. Our study evaluates the clinical features and polysomnographic (PSG) variables that predict post-operative outcomes in children with an obstructive apneal hypopnea index (AHI) of more than 25 events/hr. In this study from a single tertiary care center, we performed a retrospective chart review of patients with an AHI > 25/hr, who underwent tonsillectomy and ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Adenotonsillectomy (AT) is the first-line treatment in children with enlarged tonsils and adenoids [ 13 ]. The predictors for post AT respiratory complications requiring intervention are children with severe OSA particularly AHI > 40/h, younger children (<2 years of age), lower oxygen saturation (SpO 2 ), and poor nutritional status which was shown in a retrospective review conducted by Saeid et al [ 14 ]. For children where surgery is not indicated or desired, or for those with postoperative residual OSAS, positive airway pressure (PAP) therapy can be an effective treatment [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adenotonsillectomy (AT) is the first-line treatment in children with enlarged tonsils and adenoids [ 13 ]. The predictors for post AT respiratory complications requiring intervention are children with severe OSA particularly AHI > 40/h, younger children (<2 years of age), lower oxygen saturation (SpO 2 ), and poor nutritional status which was shown in a retrospective review conducted by Saeid et al [ 14 ]. For children where surgery is not indicated or desired, or for those with postoperative residual OSAS, positive airway pressure (PAP) therapy can be an effective treatment [ 15 ].…”
mentioning
confidence: 99%
“…Magnusdottir and colleagues performed secondary analyses of the results from the CHAT study to determine if there are factors that could predict which children with mild OSA are likely to have spontaneous resolution of OSA using cardiopulmonary coupling signals based on symptoms and PSG. They showed that those with higher baseline sleep quality, mild OSA, normal body weight, higher executive function score, and better quality of life were more likely to have spontaneous resolution of OSA [ 14 ]. Clearly, this needs to be evaluated prospectively.…”
mentioning
confidence: 99%